Test of antimicrobial activity of morpholine 2-(5-(3- fluorophenyl) -4-amino-1,2,4-triazol-3-ilthio) acetate (BKP- 115) by experimental model of pancreatitis in rats - Bigdan, O. A.; Parchenko, V. V.; Kyrychko, B. P.; Zvenigorodska, T. V.; Gutyj, B. V.; Gunchak, A. V.; Slivinska, L. G.; Savchuk, L. B.; Nazaruk, N. V.; Kit, L. P.; Dashkovskyy, O. O.; Guta, Z. A.; et al. (Bogdan Chmelnitskiy Melitopol state pedagogical university, 2020)
The purpose of this research was to study the anti-inflammatory properties of morpholine 2-(5-(3-fluorophenyl) -4-amino-1,2,4- triazol-3-ylthio) acetate (BKP-115) in intramuscular and intragastric introduction on the model of experimental pancreatitis in rats. Determination of the anti-inflammatory activity of the substance morpholine 2- (5- (3-fluorophenyl)-4-amino-1,2,4-triazol-3-ylthio) acetate was performed on 68 male rats with a starting weight of 180-200 g, which were kept in standard vivarium conditions. Since the main chain of pathogenesis of AP is the activation and influence of proteolytic enzymes of the pancreas, the toxic-infectious model was chosen – the introduction of trypsin into the tissue of the pancreas. The introduction of trypsin in animals resulted in pancreatitis with endogenous intoxication, inflammation of the tissue of the pancreas and violation of the liver functional state. As a result, one animal died in the positive control group. Prophylactic i/g and i/v injection of the BKP-115 substance contributed to a significant reduction in the content of MAW (molecules of average weight) and CIM (circulating immune complexes) in animals from control and intact groups, indicated a decrease in the level of endogenous intoxication and detoxification properties of tested substance. The highest effectiveness of BKP-115 was registered after intragastric injection. Animals from this group had similar parameters with animals injected by “Contryven” and from intact control. Intramuscular injection of BKP-115 had therapeutic effect on experimental pancreatitis and endogenous intoxication, but it was less effective after intragastric injection and had weaker efficiency than “Contryven”.
Keywords: experimental pancreatitis; experimental pancreatitis; 1,2,4-triazole derivatives